Teaching Practice at Undergraduate Level: A Comparative Analysis of Policies Across Universities in Nepal - Timsina, Jib Nath (Education Quarterly, 2024)
Teaching Practice (TP) is one of the important components of teacher education programs run by universities in Nepal. The program aims to equip student teachers with hands-on experience using better teaching techniques, classroom management, lesson planning, and reflective practice. A qualitative analysis of teaching practice policies in the Bachelor of Education (B.Ed.) programs at three Nepalese universities—Tribhuvan University (TU), Midwest University (MWU), and Far Western University (FWU) was conducted. The universities were chosen purposively based on the highest enrollment in teacher education programs. The data were examined to compare the essential activities required for TP and the distribution of evaluation marks across the universities. The findings show that the activities within TP were primarily common across universities, and very few activities were found to be university-specific. Varied pass marks and examination marking schemes were noted. The study emphasizes evidence-based evaluation and highlights the potential implementation challenges of assigning the activities.